Copper-manganese-based fiber catalytic material as well as preparation method and application thereof
By grafting amine-based functional groups on acrylic fibers and preparing copper-manganese-based fiber catalytic materials, multiple problems in existing catalysts in industrial applications have been solved, significantly improving catalytic performance and water vapor resistance.
Patent Information
- Application Number
- CN202411477534.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-12-11
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-22
AI Technical Summary
In industrial applications, existing supported metal oxide catalysts have problems such as difficult morphology, difficulty in filling, large internal diffusion of catalytic active sites, and easy blockage of reaction intermediate products. In addition, the organic fiber catalysts have insufficient thermal oxidation and water vapor resistance.
Copper-manganese fiber catalytic material is prepared by grafting amino functional groups on acrylic fibers, supporting copper and pre-oxidizing and potassium permanganate in situ oxidation, and finally ozone in situ activation using ozone gas stream.
The number of exposures of the catalyst surfactant sites is improved, the catalytic performance is enhanced, the thermal oxidation and water vapor resistance is improved, and the problem of low activity or inactivation caused by the cover of the catalyst active sites is solved.
Smart Images

Figure HDA0005096510700000011 
Figure HDA0005096510700000012 
Figure HDA0005096510700000013
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new materials, and specifically relates to a copper-manganese-based fiber catalytic material and a preparation method and application thereof. Background Art
[0002] In recent years, research in the field of functionalizing common textile fibers (synthetic and natural fibers) to keep the original characteristics and advantages of the fibers while also having various special properties and uses has attracted increasing attention. Textile fibers are in sufficient supply, of various varieties, and at reasonable prices, and are a good source of raw materials for obtaining new materials. Chemical modification is an important means of functionalizing fibers. Through the chemical reaction of the active chemical groups carried by the fibers with certain molecules or ions, or through the chemical reaction assisted by ultrasound, microwaves, or heat, the fibers have new surface chemical properties, thus having new functions such as antistatic, water absorption and moisture retention, adsorption and separation, antibacterial deodorization, and catalysis. Chemical modification can be achieved using different fibers as raw materials through different treatment methods and processes. At present, most of the supported metal oxide catalysts are based on porous materials such as metal oxides or molecular sieves. Although the catalysts prepared with these substrate materials have excellent stability and dispersibility, their morphology is not easy to change and difficult to fill in industrial applications. In addition, most of the active sites of molecular sieve or metal oxide-based catalysts are located inside the particles. In the actual reaction process, the internal diffusion process has a greater impact on the catalytic performance. At the same time, the intermediate product particles generated by the reaction are easily deposited in the catalyst pores to block them, resulting in reduced catalyst activity. Studies have shown that the rich acid-base microenvironment on the catalyst surface is of great significance for improving the catalytic performance of the catalyst. Nevertheless, due to the participation of organic polymer fibers, the active sites of the prepared catalyst will be more or less covered by organic fragments or inactive components, but they cannot be activated by high-temperature oxidation like inorganic carriers, resulting in fewer active sites on the prepared fiber surface and serious coverage by organic fragments, resulting in significantly lower catalytic activity than similar inorganic carrier catalysts. In addition, the literature "Duan W, Tang K, Zhao L, et al. MnO xNanoparticle-loaded polyacrylonitrile fibers for efficient catalytic ozonation of toluene[J]. Atmospheric Pollution Research, 2024, 15 (5): 102079” The study showed that in the process of catalytic ozone oxidation degradation of toluene using polymer fibers loaded with manganese oxide, the polymer fiber carrier was degraded, and water vapor had an inhibitory effect on the catalytic activity of the fiber catalyst. Although the inhibitory effect was reversible, water vapor is one of the influencing factors widely present in actual exhaust gas. Therefore, for organic fiber catalysts, when they are used to catalyze ozone oxidation reactions, their thermal oxidation resistance, water vapor resistance and catalytic activity need to be further improved. Summary of the invention
[0003] In view of the problems and shortcomings in the prior art, the purpose of the present invention is to provide a copper-manganese-based fiber catalytic material and a preparation method and application thereof.
[0004] To achieve the purpose of the invention, the technical solution adopted by the present invention is as follows: The first aspect of the present invention provides a method for preparing a copper-manganese-based fiber catalytic material, comprising the following steps: (1) Loading copper ions on polymer fibers to obtain copper-loaded polymer fibers; (2) pre-oxidizing the copper-loaded polymer fiber to obtain a pre-oxidized copper-loaded polymer fiber; in-situ oxidizing the pre-oxidized copper-loaded polymer fiber using a potassium permanganate in-situ oxidation method to obtain a copper-manganese-based polymer fiber catalytic material precursor; (3) The copper-manganese-based polymer fiber catalyst material precursor is subjected to an ozone in-situ activation treatment using an ozone gas flow to obtain a copper-manganese-based fiber catalyst material.
[0005] According to the above preparation method, preferably, in step (3), the temperature of the ozone in-situ activation treatment is 110-130°C, and the time is 6-14 hours. More preferably, the temperature of the ozone in-situ activation treatment is 110-120°C, and the time is 8-12 hours.
[0006] According to the above preparation method, preferably, in step (3), the concentration of ozone in the ozone gas flow is 10 to 40 mg / L, and more preferably, the concentration of ozone in the ozone gas flow is 10 to 30 mg / L.
[0007] According to the above preparation method, preferably, in step (3), the mass space velocity of the ozone gas flow during the ozone in-situ activation treatment is 240,000 to 1,200,000 mL / (g·h). More preferably, the mass space velocity of the ozone gas flow during the ozone in-situ activation treatment is 480,000 to 1,200,000 mL / (g·h).
[0008] According to the above preparation method, preferably, in step (1), the operation of loading copper ions on the polymer fiber is: immersing the polymer fiber in a copper ion solution, washing and drying after immersion to obtain the copper-loaded polymer fiber.
[0009] According to the above preparation method, preferably, the concentration of copper ions in the copper ion solution is 20 mg / L to 1000 mg / L; the copper ion solution is a copper sulfate solution or a copper nitrate solution. More preferably, the copper ion solution is a copper nitrate solution.
[0010] According to the above-mentioned preparation method, preferably, the operation of in-situ oxidation of the pre-oxidized polymer fiber by potassium permanganate in-situ oxidation method is: adding the pre-oxidized copper-loaded polymer fiber into potassium permanganate solution for oxidation reaction, collecting the pre-oxidized copper-loaded polymer fiber after the reaction is completed, and washing and drying the pre-oxidized copper-loaded polymer fiber to obtain a copper-manganese-based polymer fiber catalytic material precursor.
[0011] According to the above preparation method, preferably, the concentration of the potassium permanganate solution is 20-100 mmol / L, the liquid-solid ratio of the potassium permanganate solution to the pre-oxidized polymer fiber is (20-200) mL:1 g, the temperature of the oxidation reaction is 10-40 ° C, and the time of the oxidation reaction is 0.5-12 h.
[0012] According to the above preparation method, preferably, the pre-oxidation treatment is specifically: heat treating the copper-loaded polymer fiber in an oxygen-containing gas. More preferably, the heat treatment temperature is 200-250°C, the heat treatment time is 0.5-4 h; and the flow rate of the oxygen-containing gas is 100-500 mL / min.
[0013] According to the above preparation method, preferably, the pre-oxidation treatment is: placing the copper-loaded polymer fiber in an oxygen-containing gas, heating it to 200-250°C, and heat-treating it for 0.5-4 hours. More preferably, the heating rate of the heating is 2-20°C / min.
[0014] According to the above preparation method, preferably, the polymer fiber in step (1) is acrylic fiber or modified acrylic fiber.
[0015] According to the above preparation method, preferably, the modified acrylic fiber is an acrylic fiber grafted with amino groups, and the amino groups are grafted onto the acrylic fiber by reacting a polyamine compound with a -CN group in the acrylic fiber.
[0016] According to the above preparation method, preferably, the preparation method of the acrylic fiber grafted with amino groups is: adding the acrylic fiber to a polyamine compound solution for swelling treatment, reacting at 100-150°C for 1-12 hours after swelling, cooling, washing, and drying after the reaction to obtain the acrylic fiber grafted with amino groups. More preferably, the swelling treatment temperature is 60-80°C, and the swelling treatment time is 4-12 hours.
[0017] According to the above preparation method, preferably, the polyamine compound is one or more of ethylenediamine, diethylenetriamine, triethylenetetramine and polyethylenepolyamine.
[0018] According to the above preparation method, preferably, the dosage of the polyamine compound solution is: 20ml-200ml of the polyamine compound solution is added to every 1g of acrylic fiber for swelling treatment, and the mass fraction of the polyamine compound in the polyamine compound solution is 5-100%.
[0019] According to the above preparation method, preferably, the solvent of the polyamine compound solution is water, ethylene glycol, propylene glycol or glycerol.
[0020] According to the above preparation method, preferably, the amino group includes a primary amino group and / or a secondary amino group. More preferably, the nitrogen heterocycle is produced by cyclization of one or more of a cyano group, an amide group and an amine group.
[0021] The second aspect of the present invention provides a copper-manganese-based fiber catalytic material prepared using the preparation method described in the first aspect.
[0022] According to the above copper-manganese-based fiber catalytic material, preferably, the copper-manganese-based fiber catalytic material is in the form of one or more of fiber, wool, needle-punched cloth, and knitted cloth.
[0023] The third aspect of the present invention provides the use of the copper-manganese-based fiber catalytic material described in the second aspect in a catalyst.
[0024] According to the above application, preferably, the catalyst includes a catalyst in an ozone oxidation process; more preferably, the ozone oxidation includes ozone oxidation degradation of benzene series in a gas phase; the benzene series includes toluene and / or benzene; and the degradation temperature is 70-110°C.
[0025] Compared with the prior art, the present invention has the following positive and beneficial effects: (1) Due to the participation of organic polymer fibers, the active sites of the prepared catalyst will be more or less covered by organic fragments or inactive components, but it cannot be activated by high-temperature oxidation like an inorganic carrier, resulting in fewer active sites on the surface of the prepared fiber and serious coverage by organic fragments, resulting in its catalytic activity being significantly lower than that of similar inorganic carrier catalysts; the present invention uses acrylic fiber as a matrix material, and grafts rich amine functional groups on the surface of acrylic fiber by a chemical grafting method to prepare amino fiber (i.e., acrylic fiber grafted with amine groups), and then immerses the amino fiber in a copper ion solution to obtain a copper-loaded amino fiber, and then places the copper-loaded amino fiber in an air atmosphere for temperature-raising pre-oxidation to obtain The copper-loaded amine fiber is pre-oxidized, and the pre-oxidized copper-loaded amine fiber is prepared by potassium permanganate in-situ oxidation method to obtain a copper-manganese-based polymer fiber catalytic material precursor, and then the manganese-based polymer fiber catalytic material precursor is subjected to ozone in-situ activation treatment with an ozone gas flow. During the ozone in-situ activation treatment, based on the catalytic activity of part of the manganese oxide on the surface of the polymer fiber, the organic fragments covering the surface of the catalytic active sites are stripped and degraded through self-catalytic ozone oxidation, resulting in an increase in the number of exposed manganese oxide catalytic active sites on the surface of the polymer fiber catalytic material, thereby improving the catalytic performance of the polymer fiber catalytic material, and effectively solving the problem of low activity or inactivation of the catalytic material due to the covering of the catalytic active sites on the surface of the manganese-based polymer fiber catalytic material.
[0026] (2) The copper-manganese-based fiber catalytic material prepared by the present invention can be used to catalyze the ozone oxidation degradation of pollutants, such as volatile organic compounds, odor pollutants, etc., and when the copper-manganese-based fiber catalytic material of the present invention is used to degrade polluted gas with a toluene or benzene concentration of 100 ppm under the conditions of an air velocity of 120,000 mL / (g·h), a reaction temperature of 100°C, and an ozone concentration of 4.0-4.5 mg / L, the toluene or benzene removal rate reaches 96.4% to 100%. Under the same degradation conditions, when the copper-manganese-based polymer fiber material precursor that has not been activated by ozone is used as a catalyst, the toluene removal rate is only 51% to 78%. Therefore, compared with the process without ozone in-situ activation, the catalytic activity of the copper-manganese-based fiber catalytic material prepared by ozone in-situ activation treatment of the present invention is significantly improved.
[0027] (3) The copper-manganese-based fiber catalytic material of the present invention is doped with copper and manganese at the same time. On the one hand, copper can produce a strong chelating effect with the functional groups (-NH2, -NH-, etc.) in the polymer fiber, thereby playing a cross-linking role on the polymer fiber, and participates in the cross-linking cyclization of nitrogen-containing groups during the thermal oxidation process, thereby improving the thermal oxidation stability of the prepared fiber catalytic material; it solves the technical problem that the existing manganese oxide-loaded fiber catalytic material has poor thermal oxidation stability and the polymer fiber carrier is easily degraded during the catalytic ozone oxidation degradation of benzene series. On the other hand, when the existing manganese-based fiber catalyst material is used to catalyze the ozone oxidation degradation of benzene-containing gases, when the relative humidity of the benzene-containing gases increases to 20%, the removal rate of benzene is low, because the competitive adsorption of water vapor, benzene and ozone on the active sites of the catalyst dominates, resulting in a significant decrease in the removal rate of benzene; however, when the copper-manganese-based fiber catalyst material of the present invention is used to catalyze the ozone oxidation degradation of benzene-containing gases with high humidity, in the presence of water vapor, the copper species in the copper-manganese-based fiber catalyst material can provide adsorption sites for benzene, and the presence of copper is more likely to catalyze the decomposition of ozone to generate highly oxidizing hydroxyl radicals, thereby improving the performance of the polymer fiber catalyst material in catalyzing the degradation of benzene. Therefore, the introduction of copper significantly improves the water vapor resistance stability of the existing manganese-based fiber catalyst material, and solves the technical problem that when the existing polymer fiber catalyst material catalytically degrades benzene-containing gases with high humidity, water vapor inhibits the catalytic activity of the polymer catalyst material, resulting in a low removal rate of benzene. Therefore, the copper-manganese-based fiber catalytic material prepared by the present invention not only has good performance in catalytic degradation of pollutants (benzene series), but also has good thermal oxidation stability and water vapor resistance, and is more suitable for treating gases containing pollutants (benzene series) with high humidity.
[0028] (4) The present invention subjects polymer fibers to thermal oxidation treatment in an oxygen-containing gas, which can cause some functional groups on the fiber surface to cross-linking, cyclization, etc., thereby improving the thermal oxidation stability and oxidation resistance of the polymer fiber catalytic material, and solving the technical problems of poor thermal oxidation stability and poor oxidation resistance of existing manganese-based polymer fiber catalytic materials.
[0029] (5) The copper-manganese-based fiber catalytic material prepared by the present invention has stable oxidation resistance, high thermal oxidation stability, good water vapor resistance, and excellent catalytic performance. In addition, there is no restriction on the choice of form, and it can be used in any form such as random fibers, wool yarn, needle-punched cloth, knitted cloth, etc., which is not only convenient for filling, but also greatly broadens the depth and breadth of the use of the catalytic material.
[0030] (6) The preparation method of the copper-manganese-based fiber catalytic material of the present invention is simple to operate, requires mild conditions, and is easy to promote and apply industrially. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1The SEM characterization images of the copper-manganese-based fiber catalytic material precursor and the copper-manganese-based fiber catalytic material prepared in Example 1 of the present invention; wherein a1-a3 are different microscopic scale morphology images of the copper-manganese-based fiber catalytic material precursor, and b1-b3 are different microscopic scale morphology images of the copper-manganese-based fiber catalytic material; Figure 2 This is an EDS surface scan of the copper-manganese-based fiber catalytic material prepared in Example 1 of the present invention, wherein A is the microscopic morphology of the EDS surface scanning area, B is the Mn element distribution map in the scanning area, and C is the Cu element distribution map in the scanning area; Figure 3 The figure is a test result diagram of the degradation effect of copper-manganese-based fiber catalytic materials and manganese-based fiber catalytic materials on the catalytic ozone oxidation degradation of toluene in gases with different humidity; wherein a is the test result of the copper-manganese-based fiber catalytic material prepared in Example 1, and b is the test result of the pure manganese fiber catalytic material prepared according to the method recorded in the literature, X tol. represents the toluene removal rate, X ozo. Relative humidity represents the relative humidity of the gas. DETAILED DESCRIPTION
[0032] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0033] The following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0034] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. In addition, it should also be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates that there are features, steps, operations, parts and / or combinations thereof.
[0035] The experimental methods in the following examples without specifying specific conditions all adopt conventional techniques in the art or follow the conditions recommended by the manufacturers; the reagents or instruments used without specifying the manufacturers are all conventional products that can be obtained commercially.
[0036] Embodiment 1: A method for preparing a copper-manganese-based fiber catalytic material, specifically comprising: The commercial acrylic fiber was washed three times with deionized water and dried at 60°C to constant weight. 200mL of triethylenetetramine was added to a three-necked flask, and then 2g of pretreated acrylic fiber was weighed and immersed in triethylenetetramine at 60°C for swelling for 12h, then heated to 150°C for reaction for 3h, cooled, washed, and dried at 60°C to constant weight to obtain amino fiber, and its exchange capacity was measured to be 5.93mmol / g; 1g of the obtained amino fiber was soaked in 0.2L of copper nitrate solution with a copper ion concentration of 400mg / L, shaken at 25°C for 12h, washed, and dried at 60°C to constant weight to obtain copper-loaded amino fiber. Take 1g of copper-loaded amine fiber and place it in a tube furnace. Pass air into the tube furnace at 200mL / min for 30min balance. Then heat it to 200℃ at 10℃ / min and keep it constant for 4h. Cool it and seal it to obtain pre-oxidized copper-loaded amine fiber. Take 0.5g of pre-oxidized copper-loaded amine fiber and place it in a conical flask containing 100mL of potassium permanganate solution with a concentration of 25mmol / L. Keep it at 15℃ and shake it for 2h. Take it out, wash it with water until the eluate is colorless, and dry it at 60℃ to constant weight to obtain the copper-manganese-based fiber catalytic material precursor. The copper-manganese-based fiber catalytic material precursor is placed in an ozone gas flow with an ozone concentration of 20mg / L, a mass space velocity of 1200000mL / (g·h), and a temperature of 110℃ for in-situ activation for 10h to obtain the copper-manganese-based fiber catalytic material. After testing, the copper content in the copper-manganese-based fiber catalytic material is 20mg / g and the manganese content is 204 mg / g.
[0037] The copper-manganese-based fiber catalytic material and the copper-manganese-based fiber catalytic material precursor prepared in this embodiment were used to catalyze the ozone oxidation degradation of toluene in the gas; the degradation experimental conditions were: space velocity 120000 mL / (g·h), reaction temperature 100°C, toluene concentration in the gas 100 ppm, ozone concentration 4.0-4.5 mg / L, and gas humidity 0-10%. After the degradation reaction was completed, the toluene content in the gas was detected and the toluene removal rate was calculated.
[0038] It was found through testing that the removal rate of toluene in the gas by the copper-manganese-based fiber catalytic material prepared in this embodiment was 100%, while the removal rate of toluene in the gas by the copper-manganese-based fiber catalytic material precursor was 78%. This shows that the catalytic performance of the copper-manganese-based fiber catalytic material prepared in the present invention is significantly higher than that of the copper-manganese-based fiber catalytic material precursor that has not been treated with ozone in-situ activation, and can be used to catalyze ozone oxidation to degrade toluene pollutants in the gas.
[0039] Embodiment 2: A method for preparing a copper-manganese-based fiber catalytic material, specifically comprising: The commercial acrylic fiber was washed three times with deionized water and dried at 60°C to constant weight. 200 mL of diethylenetriamine solution (the mass fraction of diethylenetriamine in the diethylenetriamine solution was 20%, and the solvent of the diethylenetriamine solution was ethylene glycol) was added to a three-necked flask, and then 2 g of pretreated acrylic fiber was immersed in diethylenetriamine at 80°C for swelling for 4 h, then heated to 130°C for reaction for 5 h, cooled, washed, and dried at 60°C to constant weight to obtain amino fiber, and its exchange capacity was measured to be 4.05 mmol / g; 2 g of the obtained amino fiber was immersed in 1 L of copper sulfate solution with a copper ion concentration of 20 mg / L, shaken at 25°C for 6 h, washed, and dried at 60°C to constant weight to obtain copper-loaded amino fiber. Take 2g of copper-loaded amine fiber and place it in a tube furnace. Pass air into the tube furnace at 100mL / min for 30min balance. Then heat it to 250℃ at 20℃ / min and keep it at constant temperature for 0.5h. Cool it and seal it to obtain pre-oxidized copper-loaded amine fiber. Take 1g of pre-oxidized copper-loaded amine fiber and place it in a conical flask containing 200mL of 100mmol / L potassium permanganate solution. Keep it at 10℃ and shake it for 12h. Take it out, wash it with water until the eluate is colorless, and dry it at 60℃ to constant weight to obtain the copper-manganese-based fiber catalytic material precursor. The copper-manganese-based fiber catalytic material precursor is placed in an ozone gas flow with an ozone concentration of 30mg / L, a mass space velocity of 960000mL / (g·h), and a temperature of 120℃ for in-situ activation for 6h to obtain the copper-manganese-based fiber catalytic material. After testing, the copper content in the copper-manganese-based fiber catalytic material is 5mg / g and the manganese content is 120mg / g.
[0040] The copper-manganese-based fiber catalytic material and the copper-manganese-based fiber catalytic material precursor prepared in this embodiment were used to catalyze the ozone oxidation degradation of benzene in the gas; the degradation experimental conditions were: space velocity 120000 mL / (g·h), reaction temperature 100°C, benzene concentration in the gas 100 ppm, ozone concentration 4.0-4.5 mg / L, and gas humidity 0-10%. After the degradation reaction was completed, the benzene content in the gas was detected and the benzene removal rate was calculated.
[0041] It was found through testing that the removal rate of benzene in the gas by the copper-manganese-based fiber catalytic material prepared in this embodiment was 96.4%, while the removal rate of benzene in the gas by the copper-manganese-based fiber catalytic material precursor was 51%. This shows that the catalytic performance of the copper-manganese-based fiber catalytic material prepared in the present invention is significantly higher than that of the copper-manganese-based fiber catalytic material precursor that has not been treated with ozone in-situ activation, and can be used to catalyze ozone oxidation to degrade benzene pollutants in the gas.
[0042] Embodiment 3: A method for preparing a copper-manganese-based fiber catalytic material, specifically comprising: The commercial acrylic fiber was washed three times with deionized water and dried at 60°C to constant weight. 40 mL of ethylenediamine solution (the mass fraction of ethylenediamine in the ethylenediamine solution was 40%, and the solvent of the ethylenediamine solution was propylene glycol) was added to a three-necked flask, and then 2 g of pretreated acrylic fiber was immersed in diethylenetriamine at 60°C for swelling for 12 h, then heated to 100°C for reaction for 12 h, cooled, washed, and dried at 60°C to constant weight to obtain amino fiber, and its exchange capacity was measured to be 3.06 mmol / g; 2 g of the obtained amino fiber was immersed in 0.2 L of copper nitrate solution with a copper ion concentration of 1000 mg / L, shaken at 25°C for 2 h, washed, and dried at 60°C to constant weight to obtain copper-loaded amino fiber. Take 2g of copper-loaded amine fiber and place it in a tube furnace. Pass air into the tube furnace at 500mL / min for 30min balance. Then heat it to 220℃ at 2℃ / min and keep it at constant temperature for 2h. Cool it and seal it to obtain pre-oxidized copper-loaded amine fiber. Take 1g of pre-oxidized copper-loaded amine fiber and place it in a conical flask containing 100mL of 50mmol / L potassium permanganate solution. Keep it at 25℃ and shake it for 6h. Take it out, wash it with water until the eluate is colorless, and dry it at 60℃ to constant weight to obtain the copper-manganese-based fiber catalytic material precursor. The copper-manganese-based fiber catalytic material precursor is placed in an ozone gas flow with an ozone concentration of 10mg / L, a mass space velocity of 480000mL / (g·h), and a temperature of 115℃ for in-situ activation for 14h to obtain the copper-manganese-based fiber catalytic material. After testing, the copper content in the copper-manganese-based fiber catalytic material is 50mg / g and the manganese content is 89mg / g.
[0043] The copper-manganese-based fiber catalytic material and the copper-manganese-based fiber catalytic material precursor prepared in this embodiment were used to catalyze the ozone oxidation degradation of toluene in the gas; the degradation experimental conditions were: space velocity 120000 mL / (g·h), reaction temperature 100°C, toluene concentration in the gas 100 ppm, ozone concentration 4.0-4.5 mg / L, and gas humidity 0-10%. After the degradation reaction was completed, the toluene content in the gas was detected and the toluene removal rate was calculated.
[0044] It was found through testing that the removal rate of toluene in the gas by the copper-manganese-based fiber catalytic material prepared in this embodiment was 100%, while the removal rate of toluene in the gas by the copper-manganese-based fiber catalytic material precursor was 62%. This shows that the catalytic performance of the copper-manganese-based fiber catalytic material prepared in the present invention is significantly higher than that of the copper-manganese-based fiber catalytic material precursor that has not been treated with ozone in-situ activation, and can be used to catalyze ozone oxidation to degrade toluene pollutants in the gas.
[0045] Comparative Example 1: A method for preparing a manganese-based fiber catalytic material, specifically comprising: The commercial acrylic fiber was washed three times with deionized water and dried at 60°C to constant weight. Add 200mL of triethylenetetramine into a three-necked flask, then weigh 2g of pretreated acrylic fiber and immerse it in triethylenetetramine to swell for 12h at 60℃, then heat it to 150℃ for reaction for 3h, cool, wash, and dry at 60℃ to constant weight to obtain amino fiber, and its exchange capacity is measured to be 5.93mmol / g; take 1g of the prepared amino fiber and place it in a tubular furnace, pass air into the tubular furnace at 200mL / min for equilibration for 30min, then heat it to 200℃ at 10℃ / min and keep it at a constant temperature for 4h, cool, seal and store to obtain pre-oxidized amino fiber; take 0.5g of pre-oxidized amino fiber and put it into a conical flask containing 100mL of potassium permanganate solution with a concentration of 25mmol / L, shake it at a constant temperature of 15℃ for reaction for 2h, take it out, wash it with water until the washing liquid is colorless, and dry it at 60℃ to constant weight to obtain a manganese-based fiber catalytic material precursor. The manganese-based fiber catalytic material precursor was placed in an ozone gas flow with an ozone concentration of 20 mg / L, a mass space velocity of 1200000 mL / (g·h) and a temperature of 110°C for in-situ activation for 4 hours to obtain a manganese-based fiber catalytic material. After testing, the manganese content in the manganese-based fiber catalytic material was 219 mg / g.
[0046] The manganese-based fiber catalytic material prepared in this comparative example was used to catalyze ozone oxidation to degrade toluene in the gas; the degradation experimental conditions were: space velocity 120000 mL / (g·h), reaction temperature 100°C, toluene concentration in the gas 100 ppm, ozone concentration 4.0-4.5 mg / L, and gas humidity 0-10%. After the degradation reaction was completed, the toluene content in the gas was detected and the toluene removal rate was calculated. It was found that the manganese-based fiber catalytic material prepared in this example had a removal rate of 100% for toluene in the gas.
[0047] (I) SEM characterization of the copper-manganese-based fiber catalytic material prepared by the present invention The copper-manganese-based fiber catalytic material precursor and the copper-manganese-based fiber catalytic material prepared in Example 1 of the present invention were characterized by SEM. Figure 1 shown.
[0048] Depend on Figure 1 It can be seen that the surface of the copper-manganese-based fiber material precursor contains many particles smaller than 100 nm. After in-situ ozone activation, the small particles on the fiber surface aggregate into large particles. This is mainly because the in-situ ozone activation causes the organic fragments covering the surface of the active sites to be stripped and degraded under autocatalytic ozone oxidation, and the exposed active species aggregate to generate larger particles of active species. Although the particles of the active species become larger, the actual exposed effective site area increases due to the oxidative stripping of the organic fragments covering the surface, thereby greatly improving the catalytic performance of the fiber.
[0049] (II) EDS surface scanning characterization of the copper-manganese-based fiber catalytic material prepared by the present invention The copper-manganese-based fiber catalytic material prepared in Example 1 of the present invention was subjected to EDS surface scanning. The EDS surface scanning results are as follows: Figure 2 shown.
[0050] Depend on Figure 2 It can be seen that the surface of the copper-manganese-based fiber catalytic material prepared by the present invention contains more manganese and less copper, and is evenly distributed, which confirms that the copper and manganese active species are evenly loaded on the fiber surface, and the prepared fiber catalyst is a copper-manganese-based fiber catalytic material.
[0051] (III) Testing of water vapor resistance stability of the copper-manganese-based fiber catalytic material prepared by the present invention In order to study the water vapor resistance of the copper-manganese-based fiber catalytic material prepared in this application, the copper-manganese-based fiber catalytic material prepared in Example 1 of the present invention and the manganese-based fiber catalytic material prepared in Comparative Example 1 were used to catalyze the ozone oxidation degradation of toluene in the gas; the degradation experimental conditions were: air velocity 120000 mL / (g·h), reaction temperature 100°C, toluene concentration in the gas was 100 ppm, ozone concentration was 4.0-4.5 mg / L, and relative humidity of the gas was 65%. After the degradation reaction was completed, the toluene content in the gas was detected and the toluene removal rate was calculated.
[0052] It was found through testing that the removal rate of toluene in the gas by the copper-manganese-based fiber catalytic material prepared in Example 1 of the present invention was 100%, while the removal rate of toluene in the gas by the manganese-based fiber catalytic material prepared in Comparative Example 1 was 91%. This shows that, compared with the manganese-based fiber catalytic material, the introduction of copper makes the copper-manganese-based fiber catalytic material prepared in the present invention have good water vapor resistance stability, and is more suitable for treating pollutant (benzene)-containing gas with high humidity.
[0053] In addition, in order to further study the effect of different gas humidity on the performance of the copper-manganese-based fiber catalytic material of the present invention in catalyzing the ozone oxidation degradation of toluene in the gas, the copper-manganese-based fiber catalytic material prepared in Example 1 of the present invention was used to catalyze the ozone oxidation degradation of toluene in gases with different humidity; the degradation experimental conditions were: mass space velocity 240000 mL / (g·h), reaction temperature 100°C, toluene concentration in the gas 100 ppm, and ozone concentration 4.0-4.5 mg / L. After the degradation reaction was completed, the toluene content in the gas was detected and the toluene removal rate was calculated. The experimental results are as follows: Figure 3 As shown in a.
[0054] According to the literature “Duan W, Tang K, Zhao L, et al. MnO xNanoparticle-loaded polyacrylonitrile fibers for efficient catalytic ozonation of toluene[J].Atmospheric Pollution Research, 2024, 15 (5): 102079” was prepared by potassium permanganate direct oxidation method, and its manganese content was measured to be 215.3 mg / g. The pure manganese fiber catalyst was used to catalyze ozone oxidation to degrade toluene in gases with different humidity. The degradation experimental conditions were: mass space velocity 80000 mL / (g·h), reaction temperature 100℃, toluene concentration in gas 120 ppm, and ozone concentration 7.6-7.8 mg / L. After the degradation reaction, the toluene content in the gas was detected and the toluene removal rate was calculated. The experimental results are as follows: Figure 3 As shown in b.
[0055] Depend on Figure 3 As can be seen from a, for copper-manganese-based fiber catalytic materials, when the relative humidity of the gas increases to 56%-69% (70-160 min), the toluene removal rate increases from 0.58 to 0.71, indicating that the introduction of water vapor helps to remove toluene. This is mainly because the copper-manganese-based fiber catalytic material is more likely to catalyze the decomposition of ozone to generate highly oxidizing hydroxyl radicals in the presence of water vapor, and the manganese species mainly provide active sites for the decomposition of ozone, and the copper species mainly provide active sites for the adsorption of toluene, thereby promoting the oxidative degradation of toluene. For pure manganese polymer fiber catalysts, increasing the relative humidity will reduce the toluene removal rate, especially when the relative humidity increases to more than 20%, the toluene removal rate decreases significantly. This is mainly because the competitive adsorption of water vapor, toluene and ozone on the active sites of the catalyst dominates. Figure 3 As shown in Figure b, the toluene removal rate decreased from 77.2% to 71.6% when the relative humidity was kept constant in the first 120 min of the reaction, which was mainly caused by the adsorption of toluene by the fiber catalyst. When the relative humidity increased from 9.7% to 33.3%, the toluene removal rate remained basically unchanged; after stopping humidification, the toluene removal rate increased from 72.9% to 77.8%, which was mainly due to the upward floating of ozone concentration. At 250 min, the relative humidity was increased to 20-21% again, and the toluene removal rate dropped to 64.5%, indicating that water vapor had an inhibitory effect on the catalytic reaction. Therefore, the introduction of copper significantly improved the water vapor resistance stability of the pure manganese polymer fiber catalyst.
[0056] The experimental results once again prove that the introduction of copper significantly improves the water vapor resistance stability of existing manganese-based fiber catalyst materials, and solves the technical problem that when the existing polymer fiber catalyst materials catalytically degrade humid benzene-containing gases, water vapor inhibits the catalytic activity of the polymer catalyst material, resulting in a low benzene removal rate.
[0057] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention, and are not intended to limit the present invention in other forms. Any technician familiar with the profession may use the above technical content as inspiration to make changes or modifications. This is an equivalent embodiment of equivalent changes. However, any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the technical concept of the present invention still fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a copper-manganese-based fiber catalytic material, characterized in that: The following steps are involved: (1) Loading copper ions on polymer fibers to obtain copper-loaded polymer fibers; (2) pre-oxidizing the copper-loaded polymer fiber to obtain a pre-oxidized copper-loaded polymer fiber; in-situ oxidizing the pre-oxidized copper-loaded polymer fiber using a potassium permanganate in-situ oxidation method to obtain a copper-manganese-based polymer fiber catalytic material precursor; (3) The copper-manganese-based polymer fiber catalyst material precursor is subjected to an ozone in-situ activation treatment using an ozone gas flow to obtain a copper-manganese-based fiber catalyst material.
2. The preparation method according to claim 1, characterized in that The temperature of the ozone in-situ activation treatment is 110-130° C., and the time is 6-14 hours; the concentration of ozone in the ozone gas flow is 10-40 mg / L, and the mass space velocity of the ozone gas flow during the ozone in-situ activation treatment is 240000-1200000 mL / (g·h).
3. The preparation method according to claim 2, characterized in that: The operation of loading copper ions on the polymer fiber is: immersing the polymer fiber in a copper ion solution, washing and drying after the immersion, so as to obtain the copper-loaded polymer fiber.
4. The preparation method according to claim 3, characterized in that: The concentration of copper ions in the copper ion solution is 20 mg / L to 1000 mg / L; the copper ion solution is a copper sulfate solution or a copper nitrate solution; the operation of in-situ oxidation of the pre-oxidized copper-loaded polymer fiber by potassium permanganate in-situ oxidation method is as follows: adding the pre-oxidized copper-loaded polymer fiber to the potassium permanganate solution for oxidation reaction, collecting the pre-oxidized copper-loaded polymer fiber after the reaction is completed, and washing and drying the pre-oxidized copper-loaded polymer fiber to obtain a copper-manganese-based polymer fiber catalytic material precursor.
5. The preparation method according to claim 3, characterized in that The concentration of the potassium permanganate solution is 20-100 mmol / L, the liquid-solid ratio of the potassium permanganate solution to the pre-oxidized polymer fiber is (20-200) mL:1 g, the temperature of the oxidation reaction is 10-40° C., and the time of the oxidation reaction is 0.5-12 h.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In step (2), the pre-oxidation treatment is specifically: heat treating the copper-loaded polymer fiber in an oxygen-containing gas, the heat treatment temperature is 200-250°C, the heat treatment time is 0.5-4 h, and the flow rate of the oxygen-containing gas is 100-500 mL / min; in step (1), the polymer fiber is an acrylic fiber or a modified acrylic fiber; the modified acrylic fiber is an acrylic fiber grafted with an amino group, and the amino group is grafted onto the acrylic fiber by reacting a polyamine compound with a -CN group in the acrylic fiber.
7. A copper-manganese-based fiber catalytic material prepared by the preparation method described in any one of claims 1-6.
8. The copper-manganese-based fiber catalytic material according to claim 7, characterized in that: The copper-manganese-based fiber catalytic material is in the form of one or more of fiber, wool, needle-punched cloth, and knitted cloth.
9. Use of the copper-manganese-based fiber catalytic material according to claim 7 or 8 in a catalyst.
10. The use according to claim 9, characterized in that: The catalyst includes a catalyst in an ozone oxidation process; the ozone oxidation includes ozone oxidation degradation of benzene series in a gas phase; the benzene series includes toluene and / or benzene; and the degradation temperature is 70-110°C.
Citation Information
Patent Citations
Ozone and formaldehyde decomposing material and preparation method therefor
CN105312048A
Efficient moisture-resistant ozonolysis catalyst and preparation method and application thereof
CN112473728A
Manganese-loaded fiber catalyst for catalytic ozonation as well as preparation method and application of manganese-loaded fiber catalyst
CN114405546A
Preparation method of catalyst for removal of volatile organic compounds adsorption and its application.
KR1020150031586A
Catalytic composite for catalytic ozonation process and the method of removing non-degradable organic material using the same
KR1020160035306A